Exame Nacional Do Ensino Médio: Análise Da Reorganização Estrutural Do Exame - Souza, Deise Lopes De [UNIFESP] (2018)
The Study Analyses The Structural And Methodological Reorganization Of The Exame Nacional Do Ensino Médio (Enem), Conducted In 2009, Searching To Understand Its Political And Educational Bases. In Addition, It Intends To Investigate The `New" Enem Conceptions Of Knowledge And Formation. In Order To Do So, The Research Had Settled As Its Main Purpose The Analysis Of Enem"S Official Documents And Legislation, Its Pedagogical Reports And Some Examination Items. The Analyses Is Based On The Theoretical Studies Of The Classic Authors Of Critical Theory Of Society And Found That: 1) Enem's Reformulation Shows No Ruptures Or Significant Changes In Political And Educational Premises That Underpinned The Exam Creation; 2) The Reformulation Was Carried Out Mainly To Use The Exam As Part Of The Public Higher Education Admission Processes And As A Reference Of Curricular Changes In High School, Both Goals Were Sought By The Government Management Bodies But Were Not Widely Performed Due To The Characteristics Of The Exam